Inquiry through Industrial Chemistry in Compulsory Secondary Education for the Achievement of the Development of the 21st Century Skills - Diez-Ojeda, María; Queiruga-Dios, Miguel Ángel; Velasco-Pérez, Noelia; López-Iñesta, Emilia; Vázquez-Dorrío, José Benito (Education sciences, 2021)
At a key moment when education systems are moving towards the development of 21st-century skills at school, we propose to develop them with a series of enquiry activities connected to the real world on the subject of Chemistry in Compulsory Secondary Education. The four selected topics have practical aspects, as they are related to industrial chemistry, and are proposed in educational practice using the 5E model. The results obtained in a pilot test with 22 students show that the context created facilitates the development of 21st century competences. It is understood that this novel proposal can be successfully employed in other contexts.